"I'm Going to Love and Tolerate the Shit Out of You": Hybrid Masculinities in the Brony Community. (April 2022) - Palmer, Zachary D.
Based on interviews with 30 men who are fans of My Little Pony and ethnographic observations at four My little Pony conventions, this article examines men's engagement with feminized media as a form of hybrid masculinities. I identify two major subgroups of fans. The first utilized the brony community as a space that expanded the norms for men around emotional expression without challenging systemic inequality and distanced themselves from privilege by aligning themselves with a "gender defying" fandom. The second and dominant group expressed an aggrieved masculinity and engaged with the community as an explicitly antifeminist project, reinterpreting the show to assert hegemonic masculinity. This article contributes to understanding how men may articulate power through their engagement with feminized media and, more generally, expands the concept of hybrid masculinities.